2019
DOI: 10.3389/fgene.2019.00982
|View full text |Cite
|
Sign up to set email alerts
|

Copy Number Variation Mapping and Genomic Variation of Autochthonous and Commercial Turkey Populations

Abstract: This study aims at investigating genomic diversity of several turkey populations using Copy Number Variants (CNVs). A total of 115 individuals from six Italian breeds (Colle Euganei, Bronzato Comune Italiano, Parma e Piacenza, Brianzolo, Nero d’Italia, and Ermellinato di Rovigo), seven Narragansett, 38 commercial hybrids, and 30 Mexican turkeys, were genotyped with the Affymetrix 600K single nucleotide polymorphism (SNP) turkey array. The CNV calling was performed with the Hidden Markov Model of PennCNV softwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 59 publications
0
28
0
Order By: Relevance
“…The genotypes of 12 birds of Parma e Piacenza (PrPc) breed from a previous study [ 18 ] are complemented in this study with 13 birds of the same breed and 78 individuals of 3 additional Italian turkey breeds (Bronzato Comune: BrCI, Ermellinato di Rovigo: ErRo, and Romagnolo: RoMa) were collected for this study within the activity of the TuBAvI project ( Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The genotypes of 12 birds of Parma e Piacenza (PrPc) breed from a previous study [ 18 ] are complemented in this study with 13 birds of the same breed and 78 individuals of 3 additional Italian turkey breeds (Bronzato Comune: BrCI, Ermellinato di Rovigo: ErRo, and Romagnolo: RoMa) were collected for this study within the activity of the TuBAvI project ( Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…The genetic variability in turkey populations has been recently studied mainly using Single Nucleotide Polymorphisms (SNPs) as markers [ 12 , 13 , 14 , 15 ] and by the analysis of mtDNA D-loop sequences [ 16 ]. Copy number variants (CNVs) in turkeys species are still poorly studied [ 17 , 18 , 19 ]. CNVs are DNA segments longer more than 50 bp (deleted or duplicated) present at a variable copy number in comparison with a reference genome and affecting gene expression [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The genotypes of all 38 hybrids and 30 Mexican turkeys used in this study are the ones previously analyzed by [ 7 ] and were obtained with the Axiom ® Turkey Genotyping Array (Affymetrix, Santa Clara, CA, USA). As we analyze previously produced data, no ethical issue applies to data production in this research.…”
Section: Methodsmentioning
confidence: 99%
“…Genomic research in turkeys quickly developed in the last years thanks to the availability of a reference genome [ 6 ] and individual sequences, which opened opportunities also in whole-genome SNP discovery. Studies characterizing the genetic/genomic variability of turkey populations using SNPs markers (including mtDNA) are still limited [ 7 , 8 , 9 , 10 , 11 ]. Among these studies, Marras et al [ 8 ] analyzed for the first time runs of homozygosity (ROH) in commercial turkey hybrids but no study is available, at best of our knowledge, on any autochthonous turkey population not under such strong artificial selection.…”
Section: Introductionmentioning
confidence: 99%
“…The stability of candidate reference genes can be evaluated using computational resources, such as geNorm (Vandesompele et al, 2002), NormFinder (Andersen, Jensen, & Ørntoft, 2004), BestKeeper (Pfaffl, Tichopad, Prgomet, & Neuvians, 2004) and qbase+ (Hellemans, Mortier, De Paepe, Speleman, & Vandesompele, 2007 (Kozera & Rapacz, 2013;Olias, Adam, Meyer, Scharff, & Gruber, 2014). Some studies have also reported the utility of nextgeneration sequencing technologies to construct copy number variation maps based on whole genomes and high-density SNP array data, which allows checking for the copy number of several genes (e.g., da Silva et al, 2018;Strillacci et al, 2019;Zhao, Han, Sun, & Zhang, 2014). Recently, it was also suggested that "universal" reference gene primers selected based on genome ultraconserved elements (UCEs) can be applied in all vertebrates and basal chordates (Hudon et al, 2019).…”
Section: Reference Gene Primersmentioning
confidence: 99%